2001
DOI: 10.1097/00001888-200102000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Administrative Relationships between Medical Schools and Community Preceptors

Abstract: A substantial proportion of U.S. medical schools have taken action to recognize preceptors as a unique faculty group. The comments received indicate that this is an active area of development in faculty affairs policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Signatures would be required to document completion of the following: (1) topics-students were to see a patient with each of the conditions listed and discuss that topic with their supervising clinician teacher, (2) procedures-students were to observe any procedure listed once, unless a greater number was required, and (3) skills-students were to perform each skill listed the number of times required. Midclerkship feedback was similarly documented.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Signatures would be required to document completion of the following: (1) topics-students were to see a patient with each of the conditions listed and discuss that topic with their supervising clinician teacher, (2) procedures-students were to observe any procedure listed once, unless a greater number was required, and (3) skills-students were to perform each skill listed the number of times required. Midclerkship feedback was similarly documented.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of many innovative approaches to documenting clinical training have shown that students are both willing and accurate in their reporting of such experiences. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Based on the theoretical frameworks of experiential learning and educational tool development, the Clinical Activities Tool (CAT) is a curricular tool and process that has been successfully used to document clinical comparability among clerkship sites and rotation blocks within a single medical school. 16 The success of the CAT for documenting LCME-required midclerkship feedback has also been reported.…”
Section: Theliaisoncommitteeonmedicalmentioning
confidence: 99%
“…As the experience of students during their EL placement is very much dependent on the site and tutor's knowledge and skills (Owen & Stupans, 2009), perhaps a solution to this problem may include adopting quality assurance of placement sites as well as tutors which may help ensure students are getting the best learning experience. This practice has been adopted by medical schools (Walling, Sutton, & Gold, 2001).…”
Section: Tutors and Placement Sitesmentioning
confidence: 99%
“…In the United States, the first 2 years of medical school are predominantly taught by basic science professors, some hired solely to teach medical students. Despite curricular pressures and changes in healthcare delivery toward outpatient settings, clinical training of third‐ and fourth‐year medical students has remained largely hospital‐based 1 . Physicians within university‐based medical centres are comfortable teaching medical students in this context, and teaching medical students is an integral part of their academic professional identity 2 .…”
mentioning
confidence: 99%
“…2 However, utilising community-based physician preceptors, who may not share the same intrinsic motivation to teach, to meet the ambulatory educational needs of medical students in their clinical years is now a firmly established trend. 1,3 Utilising preceptors, who may not share the same intrinsic motivation to teach, to meet the ambulatory educational needs of medical students in their clinical years is now a firmly established trend. As such, multiple compensation practices between medical schools and healthcare organisations have emerged.…”
mentioning
confidence: 99%